Use of ion-selective polymer membranes for an aqueous electrolyte rechargeable Li-ion-polysulphide battery - Demir-Cakan, Rezan; Morcrette, Mathieu; Tarascon, Jean-Marie (Royal Soc Chemistry, 2015)
Aqueous electrolyte Li-ion-polysulphide batteries offer great promise due to the use of low-cost and abundant raw materials. Following up on our previous studies in which we explored a totally new practical battery chemistry coupling a well-known cathode material in Li-ion batteries (i.e. LiMn2O4) with a dissolved polysulphide anode, herein we aim to further develop the system by replacing the ceramic membrane with an ion-selective polymer membrane, allowing cost-effective and higher energy density options. After tuning the osmotic movements inside the membrane, dissolved polysulphide leakage from one compartment to another is successfully eliminated. With the additional use of porous silica serving as an absorbent for sulphur-based gaseous products, a 1.5 V average voltage together with a stable cycling profile over 200 cycles at high current density regimes are easily achieved.
Keywords: H2s Removal; Performance; Cathode; Composites; Capacity; Binder; Nafion